Myth-Making: On-going Impacts of Historical Education Policy on Beliefs About Māori in Education - Hetaraka, Maia (New Zealand Journal of Educational Studies, 2022)
The history of educational policy-making in Aotearoa New Zealand is also a history in myth-making. Myths about Māori in education are deeply embedded in educational and social thought, because they have their origins in the first political interactions between Māori and Pākeha. These interactions were motivated by contradicting forces—Māori determination to participate in the changing economic and technological landscape, contrasted against British perceptions of their own cultural superiority and inherent right to rule indigenous populations. British superiority was enshrined in aggressive and racist laws that disenfranchised and dispossessed Māori of lands, resources, economies, and attempted to de-culturalise Māori. Laws were in turn translated to policy and practice that reinforced deep seeded myths that have negatively positioned Māori socially, politically and educationally. As Aotearoa New Zealand education progresses toward a commitment to teach our dual and difficult histories, it is necessary to also expose and analyse the ways negative positioning of Māori has been purposefully built into our education system. Understanding how political histories have influenced our education system may better equip education professionals to identify and question their own conscious and unconscious biases, and to challenge and change a system that has its origins racist philosophy, reinforced by policy. Education professionals who are able to deconstruct carefully fortified, damaging myth-making about Māori will be well positioned to lead authentic movement toward a shared future.

Becoming whānau: Māori and Pākehā working together on the Indigenous-led campaign,# ProtectIhumātao - Hancock, Frances; Newton, Pania (Ethnicities, 2022)

Tikanga as the First Law of New Zealand: An Important Cognitive Shift - Fox, Caren (Amicus Curiae, 2022)

The crisis of policy failure or the moral crisis of an idea: colonial politics in contemporary Australia and New Zealand - O’Sullivan, Dominic (Political Science, 2022)
When analysing Indigenous public policy, crisis is best seen as the moral crisis of an enduring idea rather than the crisis of sporadic and unconnected instances of policy failure. In Australia and New Zealand, states use manufactured crises of Indigenous personal deficiencies to justify colonial authority. A justification which may be countered by positioning colonialism itself as the point of crisis. From this perspective, the crisis in Indigenous public policy is not resolved by the state becoming better at policy-making or more attentive to the egalitarian distribution of public resources. Instead, it is in the non-colonial possibilities of Indigenous self-determination that paths beyond crisis may lie. In practical terms, by ensuring spaces of independent Indigenous authority alongside spaces of distinctive culturally framed participation in the public life of the state. The potential for such arrangements in Australia is discussed with reference to a proposed First Nations’ Voice to Parliament and possible treaties between First Nations and the state. For New Zealand, their potential is discussed with reference to te Tiriti o Waitangi’s affirmation of independent Māori authority (rangatiratanga) and substantive state citizenship.
Keywords: Aboriginal Australians; Authority; Citizenship; Colonialism; Crises; Crisis theory; Egalitarianism; Indigenous peoples; Justification; Legislatures; Maoris; Policy making; Positioning; Public life; Public policy; Self determination; State; Treaties; colonialism; indigenous politics; indigenous self-determination; māori politics; political crisis; treaty of waitangi

‘Why would you give your children to something you don’t trust?’: Rangatahi health and social services and the pursuit of tino rangatiratanga - Lindsay Latimer, Cinnamon; Le Grice, Jade; Hamley, Logan; Greaves, Lara; Gillon, Ashlea; Groot, Shiloh; Manchi, Madhavi; Renfrew, Larissa; Clark, Terryann C. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2022)
Persistent health inequities between rangatahi Māori (Indigenous young people) and other young people within Aotearoa New Zealand are incurred by a colonial machinery of institutions, service systems and sociocultural contexts that facilitates the marginalisation of Māori. Despite a skilled and dedicated Māori workforce, current service contexts severely limit the innovation of Māori practitioners working from a basis of mātauranga Māori (Māori ways of knowing and being), and curtail their ability to support rangatahi Māori and their whānau (community of related families). We report on an interview study with 13 Māori practitioners in youth development, exploring their struggles, strengths and strategies, as part of a larger project exploring rangatahi wellbeing and whanaungatanga (connectedness and relationality). Utilising reflexive thematic analysis, we describe three conceptual domains that participant accounts spoke into: mitigating system failures to embrace rangatahi and their whānau, sustainability and longevity of services for rangatahi Māori, and fostering rangatahi tino rangatiratanga. Participant accounts illustrate the need for bold reform within youth services, towards sustainable models premised upon tino rangatiratanga – services led by Māori, designed by Māori, and intended to cater for the unique needs and aspirations of rangatahi Māori.
_eprint: https://doi.org/10.1080/1177083X.2021.1993938
Keywords: crown policy; mātauranga māori; rangatahi; tino rangatiratanga; whanaungatanga

The Critical Juncture in Aotearoa New Zealand and The Collective Future: Policy Issues in Settler/Invader Colonial Zombiism Found in “Biculturalism” - Simon, Hemopereki (International Journal of Critical Indigenous Studies, 2022)
This research examines the settler colonial legacy of Aotearoa New Zealand. It shows that biculturalism has emerged as a discursive byproduct of neoliberalism and settler colonialism. Simon’s recent work and the Te Paparahi o Te Raki Waitangi Tribunal decision aligns with the view of a significant paradigm shift since biculturalism suppresses affirmation of and mana motuhake. Biculturalism can be viewed through Moreton-Robinson’s white possessive lens as well as Beck's zombie concepts, which are used to prop up deteriorating and/or fictional social institutions. As a zombie concept in Aotearoa New Zealand, “biculturalism” supports settler/invader power structures. Indigenous communities disproportionately experience the destructive consequences of neoliberal policies and statecraft. Aotearoa New Zealand’s collective future requires abandoning biculturalism; to that end the author recommends revising common historiographic thought concerning Te Tiriti o Waitangi (Treaty of Waitangi) and the concept of “settling”.
Keywords: bicultural; colonisation; neoliberalism

Re-Imagining Wild Rivers in Aotearoa New Zealand - Brierley, Gary; Fuller, Ian; Williams, Gary; Hikuroa, Dan; Tilley, Alice (Land, 2022)
If wilderness is dead, do wild rivers exist and if so, in what form and in whose construction? This reflective article reviews perspectives on rivers in Aotearoa New Zealand as wild or tamed entities. A historical overview of the socio-cultural and institutional relationships with rivers examines the meanings of rivers in Aotearoa New Zealand through multiple lenses. This includes indigenous Māori knowledge, command-and-control mentalities of a settler society that assert human authority over rivers, the emergence of the environmental movement and associated legislation with a sustainability focus (the Resource Management Act), and recent movement towards co-governance arrangements that incorporate the original intent of Te Tiriti o Waitangi (1840). It is contended that management practices have disconnected society from rivers, and vice versa, creating a sense of environmental loss (solastalgia), especially for Māori. Using rivers in the Greater Wellington Region as examples, prospects to accommodate wild river behaviour in Aotearoa New Zealand are explored. Recognising that re-wilding is no longer a feasible option in most instances, further attempts to tame rivers are also considered to be unrealistic, especially in light of climate change and accentuated flood risk. Reconnecting with indigenous knowledge offers prospects to re-imagine wild rivers in Aotearoa, living generatively with rivers as dynamic and emergent entities.
Keywords: environmental management; mātauranga māori; river management

Why New Zealand’s Indigenous reconciliation process has failed to empower Māori fishers: Distributional, procedural, and recognition-based injustices - Bodwitch, Hekia; Song, Andrew M.; Temby, Owen; Reid, John; Bailey, Megan; Hickey, Gordon M. (World Development, 2022)
How is it that the New Zealand government’s process for re-establishing Indigenous fishing rights has failed to deliver thriving Māori fisheries? This paper examines why, at Te Waihora, a coastal lake, and site of one of the nation’s longest running and best-funded state-Māori co-governance agreements, Māori fishers have been unable to use their rights to support their fishery. As of 2018, the lake’s culturally and ecologically significant eel population was no longer commercially viable, a decline fishers have attributed to rampant dairy industry expansion upstream. Drawing on environmental justice literatures, we deploy a multi-dimensional framework to identify factors shaping possibilities for justice in the wake of rights reconciliation, as experienced by Māori fishers, scientists, and leaders. We engage theories of political economic relations to interpret the implications of these experiences for environmental justice theory and politics. Ethnographic accounts demonstrate that the New Zealand government’s process for re-establishing Māori rights falls short of achieving distributional, procedural, and recognition-based dimensions of environmental justice, and that these effects are interlinked. In particular: (i) downstream fishers are placed to bear disproportionate costs of runoff from upstream land use change; (ii) Māori fishers have little influence over governance decisions that affect land use; and (iii) government claims, including that Māori should, “move beyond grievance mode,” obscure logics for resistance. We suggest that the government’s support for dairy industry expansion represents an attempt to mitigate crises of overaccumulation, characteristic of competitive markets. Unlike those who identify persistent injustice as a logic for turning away from the state, we argue that the recurring nature of these crises, and the role state organizations play in directing responses, indicates a rationale for continued engagement with state governing bodies to advance justice.
Keywords: co-governance; economic aspects; environmental justice; equity; fisheries

Māori Academic Challenges: Delivering Mātauranga Māori During COVID-19 - Te Momo, Fiona (Journal of Contemporary Issues in Education, 2022)
In March 2020, the COVID-19 pandemic disrupted academic educational programmes in universities across the world, including Aotearoa New Zealand. For Māori academics who implement mātauranga Māori as a pedagogy, it became theoretically and practically challenging teaching virtually and online. The Te Taha Tinana, of Te Whare Tapa Wha model, created by aDurie in 1984 (Health Navigator, 2022) regarding the four dimensions of well-being, focuses on the physical presence, physical embodiment, and physical behaviour. This could not be easily taught virtuality through a computer screen during COVID-19 lockdown. For Māori academics transitioning from teaching Mātauranga Māori in person to an online environment brought forth these challenges. The challenges re-emerged in August 2021 when New Zealand went into Level 4 lockdown overnight because of the new COVID-19 Delta Virus variant. In 2022, the Omicron variant caused many universities in Aotearoa New Zealand to continue their first semester teaching online.
Keywords: covid-19; education; mātauranga māori; political development; social development; whanaungatanga

Reanimating the strangled rivers of Aotearoa New Zealand - Brierley, Gary J.; Hikuroa, Daniel; Fuller, Ian C.; Tunnicliffe, Jon; Allen, Kristiann; Brasington, James; Friedrich, Heide; Hoyle, Jo; Measures, Richard (WIREs Water, 2022)
Contemporary management practices have artificially confined (strangled) river systems in Aotearoa New Zealand to support intensified land use in riparian areas. These practices work against nature, diminishing the functionality and biodiversity values of living rivers, and associated socio-cultural relations with rivers. River confinement can accentuate flood risk by promoting development in vulnerable locations and limiting the flexibility to adapt to changing climate, prospectively accentuating future disasters. To date, uptake of space-to-move management interventions that seek to address such shortcomings is yet to happen in Aotearoa New Zealand. This is despite the fact that such practices directly align with Māori (indigenous) conceptualizations of rivers as indivisible, living entities. Treaty of Waitangi obligations that assert Māori rights alongside colonial rights of a settler society provide an additional driver for uptake of space-to-move initiatives. This article outlines a biophysical prioritization framework to support the development and roll out of space-to-move interventions in ways that work with the character, behavior, condition, and evolutionary trajectory (recovery potential) of each river system in Aotearoa. This article is categorized under: Water and Life > Conservation, Management, and Awareness Science of Water > Water and Environmental Change
Keywords: environment; environmental protection; mana moana; mana tupuna; mana whenua; mātauranga māori; tikanga | indigenous law; water management

Mana motuhake, Indigenous biopolitics and health - Hokowhitu, Brendan; Oetzel, John; Jackson, Anne-marie; Simpson, Mary; Ruru, Stacey; Cameron, Michael; Zhang, Yingsha; Erueti, Bevan; Rewi, Poia; Nock, Sophie; Warbrick, Isaac (AlterNative: An International Journal of Indigenous Peoples, 2022)
The majority of Indigenous health models do not directly acknowledge that health is a contested political space. Providing a Foucauldian analysis, this article suggests a function of biopower is to naturalise discourses such as the poor M?ori health statistic to appear based on factual evidence and thus are apolitical. Employing Foucault?s triad of power?sovereign, disciplinary and biopower?to understand the genealogy of M?ori health, this article proffers mana motuhake (M?ori political self-governance) as an appropriate health analytic because it, first, identifies Indigenous health as political and, second, because it recognises the disempowering role that colonialism has played in relation to M?ori biopolitical self-governance. Hence, we suggest M?ori health will be enhanced by mana motuhake and that research underpinned by Indigenous agency and self-governance resists biopower. The article references two Ageing Well National Science Challenge?funded research projects because they innovatively fundamentalise mana motuhake and politics to Indigenous health.
Keywords: mana motuhake; māori health

Adaptation and implementation processes of a culture-centred community-based peer-education programme for older Māori - Simpson, Mary Louisa; Ruru, Stacey; Oetzel, John; Meha, Pare; Nock, Sophie; Holmes, Kathrine; Adams, Hariata; Akapita, Ngapera; Clark, Marama; Ngaia, Kawarau; Moses, Reuben; Reddy, Rangimahora; et al. (Implementation Science Communications, 2022)
Health inequities experienced by kaumātua (older Māori) in Aotearoa, New Zealand, are well documented. Examples of translating and adapting research into practice that identifies ways to help address such inequities are less evident. The study used the He Pikinga Waiora (HPW) implementation framework and the Consolidated Framework for Implementation Research (CFIR) to explore promising co-design and implementation practices in translating an evidence-based peer-education programme for older Māori to new communities.
Keywords: health inequity; research

Māori Issues 2020-2021 - Mutu, Margaret (The Contemporary Pacific, 2022)

Disaster? No surprise - Winter, Christine J. (Environmental Politics, 2022)
I argue environmental disasters are an inevitable outcome of the underdevelopment of Western philosophy. Human induced environmental disasters are unfortunate, an unintended consequence of focusing on economic maximization in a culture without comprehensive, clearly accepted, and operationalized frameworks for environmental and intergenerational justice. However, they are of no surprise to Indigenous Peoples relegated to margins of political influence. Grounding this claim, I examine the New Zealand High Court case Greenpeace and Te Whanau-ā-Apanui vs the Minister for Energy. Case documents afford comparisons between the complex philosophic, legal, and cultural framework of Māori, that protect human and nonhuman from human-induced environmental disaster, and the dominant Anglo framings. I observe a philosophical deficit underpinning the legal and political system of Aotearoa that impedes environmental intergenerational justice. These philosophic foundations, intentionally or not, promote environmental disaster and – nationally and internationally – claim a dominant position over Indigenous systems.
_eprint: https://doi.org/10.1080/09644016.2020.1865726
Keywords: disasters; environment; environmental justice; liberalism

Mana whenua, mana moana, mana tinana, mana momona - Gillon, Ashlea; Le Grice, Jade; Webber, Melinda; McIntosh, Tracey (New Zealand Sociology, 2022)
The ways in which we understand bodies and fatness are complex. While coloniality unduly influences and shapes normative meanings of the body in everyday contexts, Maori conceptualisations of the b...
Keywords: identity; self-identification; te ao Māori

Anti-Colonial Abolitionism: International Context - Pranteau, Sheri; McIntosh, Tracey; Anthony, Thalia; Chartrand, Vicki (Journal of Prisoners on Prisons, 2022)
Keywords: colonisation; crown policy; prison abolition; racism; systematic racism

Where to for collaboration in land and water policy development in Aotearoa New Zealand? Guidance for authorising agencies - Kirk, Nicholas; Robson-Williams, Melissa; Bammer, Gabriele; Foote, Jeff; Butcher, Lian; Deans, Neil; Harmsworth, Garth; Hepi, Maria; Lilburne, Linda; Nicholas, Barbara; Small, Bruce; Turner, James A.; et al. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2022)
For the past decade, collaboration has been the preferred method of devising land and water policy in Aotearoa New Zealand to achieve agreed outcomes. However, the use of collaboration in policymaking is at a crossroads, as some argue it is unrealistic to expect stakeholders and tangata whenua with competing interests to work in partnership on contentious policy issues. To help clarify the future direction of collaboration, this paper provides authorising agencies (those with responsibility for the policy problems) with prompts to reflect ex ante on the advantages and disadvantages of pursuing collaboration. Based on a retrospective review of collaborations in New Zealand’s land and water policymaking, and a two-day symposium with collaboration practitioners, we identify situations that are potentially less suited to collaboration owing to factors that are challenging to overcome through process design. Four issues that affect the success of collaborations are identified: the nature of the policy problem, the personal and collective qualities of those involved, power relationships, and the collaborative process. Finally, we draw together practical lessons from history, the symposium, and the literature to develop a list of questions for authorising agencies to use to reflect on the advantages and disadvantages of pursuing collaboration.
Keywords: co-governance; land policy; policy; water management

Indigenous environmental defenders in Aotearoa New Zealand: Ihumātao and Ōroua River - Mika, Jason Paul; Dell, Kiri; Elers, Christine; Dutta, Mohan; Tong, Qing (AlterNative: An International Journal of Indigenous Peoples, 2022)
This article theorises the question?what is the role and nature of Indigenous environmental defenders in Aotearoa New Zealand? We explore M?ori?the Indigenous people of Aotearoa New Zealand?who act as environmental defenders of their lands and waters despite the perpetual insecurity of their constitutional rights and imbalances in power and resources compared with state and corporate actors. The environmental defence of Aotearoa New Zealand by M?ori began with the arrival of European explorers? intent on overturning Indigenous institutions of environmental management that has sustained their peoples for a thousand years. Stemming from case study analysis of M?ori environmental defenders at Ihum?tao in M?ngere and ?roua River in Manawat?, we propose whenua (land) resilience theory to explain the concomitance of environmental defence and development from an Indigenous perspective.
Keywords: colonisation; environment; kaitiakitanga; land protection

Maori identity and "political arithmetick" : the dynamics of reporting ethnicity - Kukutai, Tahu (2022)
Thesis (M. Soc.Sc. Demography)–University of Waikato, 2001. Includes bibliographical references (leaves 193-203)
Keywords: crown policy; ethnic identity; ethnicity

The future of Māori health is here – The 2022 Aotearoa New Zealand health reforms - Ahuriri-Driscoll, Annabel; Lovell, Sarah; Kawa, Deborah Te; MacDonald, Lindsey Te Ata o Tū; Mathias, Kaaren (The Lancet Regional Health – Western Pacific, 2022)
Keywords: health; healthcare system; rangatiratanga

Tracing Opuatia: Repatriating and repurposing colonial land data - Kukutai, Tahu; Whitehead, Jesse; Kani, Heeni (New Zealand Geographer, 2022)
Māori land data produced through colonial systems of dispossession lack interoperability, preventing kin-based communities from tracking their land. Our novel approach to repatriate and harmonise historic land data traces the history of the 45,500 acre Opuatia Block allocated to hapū Ngāti Tiipa in 1866, following the confiscation of 1.2 million acres of Waikato land. Ngāti Tiipa resisted Crown and settler pressures for 30 years, but 80% of Opuatia was alienated within a decade. We discuss the devastation of ‘judicial raupatu’ and the implications of this work for hapū data sovereignty and wider international efforts to achieve Indigenous data sovereignty.
Keywords: colonisation; data sovereignty; hapū; indigenous data sovereignty; iwi; māori land data; repatriation

Does the crown minerals act undermine partnership with Maori? - Billington, Carl (Public sector (Wellington), 2022)
The Crown Minerals Act 1991 (CMA) was introduced "to promote prospecting for, exploration for, and mining of Crown owned minerals for the benefit of New Zealand". A series of fundamental questions has emerged as to whether the Act undermines the ability of the Crown and tangata whenua, anchored in Te Tiriti o Waitangi, to operate in a true sense of partnership. Carl Billington takes a closer look.
Keywords: crown lands; crown policy; land tenure; law; legislation; mines and mineral resources; mining law; tiriti o waitangi/treaty of waitangi; treaty obligations

Maori crown relationships: Working with IWI in ways that enhance capability - Bargh, Maria; Birch, Nicky (Public sector (Wellington), 2022)
The emphasis on strengthening Maori Crown relationships in the Public Service Act 2020 and the establishment of Te Arawhiti signalled a new era in the public service's interactions with tangata whenua. Carl Billington investigates whether this is changing the way public sector agencies approach their interactions with Maori.
Keywords: administration; crown; kāwanatanga; planning; project management

‘Colonised by a rich pākehā’: the metaphorical characterisation of the Internet Mana alliance - Peters, Rachel; Hocking, Darryl (Media International Australia, 2022)
In 2014, the Internet Mana alliance unsuccessfully ran in the New Zealand general election gaining just 1.42% of the party vote and failing to secure an electorate seat. The leaders of the alliance attributed their poor election result to the narratives constructed by the mainstream media, which they believed negatively influenced the public?s perception of Internet Mana. This study agrees that the mainstream media was complicit in the alliance?s poor election result, and drawing upon the discourse dynamics framework for metaphor analysis, it shows how these potentially damaging public narratives were predominantly constituted through complex sets of systematic metaphors which together created broader schematic frames or conceptual scenarios and carried certain evaluative and attitudinal perceptions. This analysis shows how systematic metaphors such as the internet mana alliance is a marriage of convenience and the internet mana alliance is a colonial trade were used to construct a negative public narrative.
Keywords: colonisation; elections; mainstream media; political parties

Decolonizing politics with insights from Indigenous Studies - Bargh, Maria (Identities, 2022)
Keywords: colonisation; decolonisation; education; mātauranga māori; rangatiratanga; tikanga | indigenous law